STUDY OF USING PULSING AND PACKAGING ON ROSE CUT FLOWERS TO PROLONG VASE LIFE - Desy Nofriati; Rokhani Hasbullah (BPFP Faperta UNIB, 2012)
Using pulsing on rose cut flowers before storage and transportation should be done to kept its quality after storage. The objective of the study is to find out the composition of the pulsing to prolong the vase life. The flowers were harvested from the field when the flower was at two bud opening stages and then were pulsed with chemical solution. The experimental design used RAL and data analyzed with Analisis of Variant (ANOVA). If found out significant between treatment then continued by Duncan test. The result indicated that pulsing 3% sucrose + 25% glyserin + 300 ppm Na-Benzoat + 375 ppm sitrat acid was the best composition and decrease deterioration about 2.5% until day-3 vase life. Each flower was placed in the boxes of 60 x 15 x 7 cm3 with capacity of 20 rose cut flowers. Package with the ventilation of 3.5 cm in diameter and closed with the film polipropilen was the best design package which prolonged vase life until 5 days after storage and decrease senescence up to 20-25 0/o.The periode of flowers vase life could be extended and quality after storage could be maintained by applying those treatment.